Yeast Nab3 Protein Contains a Self-assembly Domain Found in Human Heterogeneous Nuclear Ribonucleoprotein-C (hnRNP-C) That Is Necessary for Transcription Termination - Loya, Travis J. (American Society for Biochemistry and Molecular Biology, 2013)
Nab3 is an RNA-binding protein whose function is important for terminating transcription by RNA polymerase II. It co-assembles with Nrd1, and the resulting heterodimer of these heterogeneous nuclear ribonucleoprotein-C (hnRNP)-like proteins interacts with the nascent transcript and RNA polymerase II. Previous genetic analysis showed that a short carboxyl-terminal region of Nab3 is functionally important for termination and is located far from the Nab3 RNA recognition domain in the primary sequence. The domain is structurally homologous to hnRNP-C from higher organisms. Here we provide biochemical evidence that this short region is sufficient to enable self-assembly of Nab3 into a tetrameric form in a manner similar to the cognate region of human hnRNP-C. Within this region, there is a stretch of low complexity protein sequence (16 glutamines) adjacent to a putative α-helix that potentiates the ability of the conserved region to self-assemble. The glutamine stretch and the final 18 amino acids of Nab3 are both important for termination in living yeast cells. The findings herein describe an additional avenue by which these hnRNP-like proteins can polymerize on target transcripts. This process is independent of, but acts in concert with, the interactions of the proteins with RNA and RNA polymerase and extends the relationship of Nab3 as a functional orthologue of a higher eukaryotic hnRNP.